Pemanfaatan Database Online Perpustakaan Universitas Islam Negeri Sumatera Utara Sebagai Sumber Informasi Bagi Pemustaka - Siti Lutfia Hutabarat; Fildzah Hani; Ella Trafera Mesyah; Edi Rahmadani; Nurbaiti Nurbaiti (Universitas Katolik Widya Karya Malang, 2023)
The North Sumatra State Islamic University Library has developed an online database system to store and share information resources with users. This article discusses the use of the online database provided by UIN SU Library as a source of information for users. Utilization of online databases can provide several advantages for users, such as easy and fast access to various sources of information, flexibility to access databases from anywhere and anytime, and the availability of complete and up-to-date information resources. The online database of UIN SU Library includes various types of information sources, such as electronic books, electronic journals, theses, dissertations, and other digital collections. Research objectives in abstract journals utilizing online databases may vary depending on the focus and scope of the research being conducted. However, some of the general goals of online database utilization research are to understand users' use of online databases, evaluate the quality and effectiveness of online databases, and increase the use of online databases for specific purposes. The research methodology in the abstract of online database utilization journals usually includes several stages, namely identification of research objectives, data collection, analysis of database use, evaluation of database quality and interpretation of results.